Novel ceramic fibre - Zirconium diboride composites for solar receivers in concentrating solar power systems. (1st August 2022) - Zoli, Luca; Failla, Simone; Sani, Elisa; Sciti, Diletta
Abstract: Ultra-high temperature ceramic matrix composites (UHTCMCs) are a new class of composites which combine boride phases with carbon fibres to achieve new structural and functional properties and were originally designed for aerospace applications. For the first time, this work investigates the optical response of UHTCMCs in view of their possible application as high temperature solar absorbers in Concentrating Solar Power systems. Carbon fibre-reinforced ZrB2 pellets with different fibre type and arrangement were manufactured and characterized from the point of view of optical properties and surface microstructure. The composites had high fractions of ZrB2 (∼40 vol%) and carbon fibres (up to 60 vol%). Spectral hemispherical reflectance in the range 0.3–16 μm wavelength was assessed and compared to pure boride and graphite phases. Irrespective of the fibre architecture, the solar absorptance significantly increased with respect to the pure boride, reaching or even overpassing the solar absorptance of silicon carbide. Thermal emittance, calculated from 800 K to 1500 K temperature, increased as well in comparison to the pure boride, but always remained lower than that of SiC. These optical properties, combined with structural damage tolerance and light weight, suggest that UHTCMCs are of great interest as high temperature solar absorbers, overpassing the weaknesses of current solar receivers, as well as those of the most promising alternative materials to date.